ChemInform Abstract: Construction of Vicinal Quaternary Stereogenic Centers by Enantioselective Direct Mannich‐Type Reaction Using a Chiral Bis(guanidino)iminophosphorane Catalyst. Issue 32 (July 2016) - Takeda, Tadahiro; Kondoh, Azusa; Terada, Masahiro
Abstract: The title transformation is based on the generally highly diastereoselective and highly enantioselective reaction of α‐iminophenylacetate esters with α‐substituted thionolactones.